2008
DOI: 10.1177/1553350608328866
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy After Gastric Banding Removal: A Feasibility Study

Abstract: The results suggest LSG might be a reasonable choice for patients who fail LAGB. A formal study comparing LSG with other rescue procedures should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…The conversion of failed LAGB to another restrictive procedure is not presently a universal norm. We tend to agree with Giovanni Dapri and Jacques Himpens that replacing a failed restrictive procedure with another restrictive procedure is very much open to debate [25]. We believe that a failed restrictive procedure can be changed to a malabsorptive procedure; however, we think that there is a group of patients that could be candidates for conversion to LSG, like morbidly obese adolescents, patients on lifelong anticoagulation to avoid bleeding marginal ulcer complications more commonly associated with RYGB, and very-high-risk patients that are poor candidates to withstand serious complications such as bleeding and leaks as seen after RYGBP.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The conversion of failed LAGB to another restrictive procedure is not presently a universal norm. We tend to agree with Giovanni Dapri and Jacques Himpens that replacing a failed restrictive procedure with another restrictive procedure is very much open to debate [25]. We believe that a failed restrictive procedure can be changed to a malabsorptive procedure; however, we think that there is a group of patients that could be candidates for conversion to LSG, like morbidly obese adolescents, patients on lifelong anticoagulation to avoid bleeding marginal ulcer complications more commonly associated with RYGB, and very-high-risk patients that are poor candidates to withstand serious complications such as bleeding and leaks as seen after RYGBP.…”
Section: Discussionsupporting
confidence: 54%
“…It is also being looked upon as a potential solution for failed LAGB patients. Several reports have been published of using the LSG for failed LAGB with indications including weight regain, intolerable symptoms, band slippage, and esophageal dilation [6,12,22,23,25,26]. The conversion of failed LAGB to another restrictive procedure is not presently a universal norm.…”
Section: Discussionmentioning
confidence: 96%
“…Mortality after sleeve gastroplasty is small, usually less than 0.5% 13,20,29 . In our study there was a case of death due to postoperative thromboembolism, despite the use of preventive measures and anticoagulant employee.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The vertical sleeve gastroplasty is a new option for the treatment of obesity and is currently the fastest growing 13 worldwide, as a technique that keeps the gastrointestinal continuity, with less surgical time, good weight loss curve, lack of dumping syndrome (found often in gastric bypass), access to the biliary tree, no excluded stomach segment in the cavity (hindering future diagnosis of tumors), absence of malabsorption (with low levels of nutritional complications), and allowing continued operation Table 1 Table 1 Table 1 Table 1 Table 1 20 there was an average weight loss of 54-58% of the overweight five years after vertical gastroplasty . Dapri et al 21 reported a reduction in mean BMI to 34.4 kg/m2, similar to the results found in our study.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation